Perspectivas gramaticais em livros didáticos de português como língua estrangeira: um recorte documental temporal - Barbizan, Eduardo Alves de Deus (2024)
Considering the relevant increase of teaching and learning Portuguese as a Foreign Language in Brazil and abroad (FURTOSO, 2015; IZAKI GÓMEZ, 2018; GRANATO, 2022; CHAMORRO, 2022), along with the fact that the role of grammar in pedagogical activities generally appears isolated from the discursive flows (BATSTONE, 1994; LARSEN-FREEMAN, 2003; SPADA & LIGHTBOWN, 2008), this doctoral dissertation analyzes how grammar teaching activities are presented in three Portuguese as Foreign Language textbooks published over three decades and with a gap of fifteen years between each of them. More specifically, through documentary research, we have analyzed the perspective of the activities that focus on teaching Portuguese as a Foreign Language grammar, based on Batstone's (1994) proposals of grammar as product, process, and skill, to understand the movement in pedagogical activities over the years. The focus on grammar is due to the observation in the classroom practices that learners value its study. We have identified tenuous changes in the types of pedagogical activity proposals that focus on grammar, but with the potential for activities that feature greater contextualization and learners' active involvement in the process of understanding relationships between form, meaning achieved, and Portuguese as a Foreign Language grammar use.